2010
DOI: 10.1097/dbp.0b013e3181cdaa20
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occuring Psychiatric Symptoms in Children Perinatally Infected With HIV and Peer Comparison Sample

Abstract: Objective-To compare the rates of psychopathology in youths perinatally infected with HIV (N = 319) with a comparison sample of peers (N = 256) either HIV-exposed or living in households with HIV-infected family members.Method-Participants were randomly recruited from 29 sites in the United States and Puerto Rico and completed an extensive battery of measures including standardized DSM-IV-referenced ratings scales.Results-The HIV+ group was relatively healthy (73% with CD4% >25%), and 92% were actively receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 47 publications
11
110
4
Order By: Relevance
“…These latter two differences concur with a number of previous studies of this population (see Discussion). [4][5][6] Prevalence of behavioral health risks (excluding adherence) Table 2 summarizes the proportion of PHIV + and PHEU youth who met each of the study defined criteria for each of the behavioral health risks. For PHIV + youth and PHEU youth, the most frequently reported behavioral health risk was a mental health problem (26% PHIV + and 33% PHEU), most frequently with a BSI score in the at-risk or clinically significant range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These latter two differences concur with a number of previous studies of this population (see Discussion). [4][5][6] Prevalence of behavioral health risks (excluding adherence) Table 2 summarizes the proportion of PHIV + and PHEU youth who met each of the study defined criteria for each of the behavioral health risks. For PHIV + youth and PHEU youth, the most frequently reported behavioral health risk was a mental health problem (26% PHIV + and 33% PHEU), most frequently with a BSI score in the at-risk or clinically significant range.…”
Section: Resultsmentioning
confidence: 99%
“…A number of other studies have also shown that this population of youth is at high risk for mental health problems as well as sexual risk behavior. 6,41 Unfortunately, HIV-exposed but uninfected youth are often difficult to identify and monitor. They are not followed in comprehensive HIV care clinics, unless they enroll in a limited number of studies such as this one.…”
Section: Mellins Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Whether these are higher than in other patient groups with chronic medical conditions, HIV‐exposed but uninfected siblings or well‐matched healthy controls is yet to be fully determined 222, 224, 225, 226. Nevertheless, it is essential that the multidisciplinary team at least monitor for symptoms and signs of psychological distress and mental health disorder, as children progress into adolescence and young adult life.…”
Section: Adolescence Mental Health and Transitionmentioning
confidence: 99%
“…attention deficit hyperactivity disorder), and emotional disorders (e.g. anxiety and depressive disorders) [3][4][5][6][7][8] Psychiatric disorders among children and adolescents with HIV leads to psychological distress and impaired quality of life, increased stigma and isolation and may lead to negative clinical and behavioral outcomes. Despite antiretroviral therapy improving the survival of HIV-infected children, the mental health problems of these children and adolescents have had less attention [9].…”
Section: Introductionmentioning
confidence: 99%